2018
DOI: 10.1016/j.jsv.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for predicting rotor broadband noise due to turbulent boundary layer ingestion

Abstract: A semi-empirical analytical model is developed that predicts the noise produced by a rotor ingesting a boundary layer in proximity to a hard-wall. The rotor boundary layer ingestion noise source is an important source to include when a rotor is installed close to an aircraft fuselage. This is the case for a tail mounted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…The partial blade-to-blade correlation leads to narrow-band noise around harmonics of the blade-passing frequency, also known as haystacking. In this paper, we have shown that previous derivations of Amiet's theory did not agree on a key calculation in order to account for blade-to-blade correlation of the noise sources (Paterson & Amiet 1979;Amiet 1989;Karve et al 2018). A corrected derivation of the time between blade chops of the same turbulent eddy as heard by the observer was presented.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The partial blade-to-blade correlation leads to narrow-band noise around harmonics of the blade-passing frequency, also known as haystacking. In this paper, we have shown that previous derivations of Amiet's theory did not agree on a key calculation in order to account for blade-to-blade correlation of the noise sources (Paterson & Amiet 1979;Amiet 1989;Karve et al 2018). A corrected derivation of the time between blade chops of the same turbulent eddy as heard by the observer was presented.…”
Section: Discussionmentioning
confidence: 92%
“…Karve et al (2018) used Amiet's model to show that theoretical predictions agree reasonably well with experimental results for noise generated due to turbulent boundary layer ingestion. However, Amiet (1989) and Karve et al (2018) disagree on the calculation of the time between blade chops. In this paper, we derive this result in a simple and clear way, and identify the correct form by comparing far-field noise predictions against the rotational model of turbulence ingestion noise.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In order to allow for a thorough noise assessment of such vehicles, a crucial step is the investigation of the noise emission of the technological features on the component level and, based on such investigations, the development of source models that can be incorporated into scientific noise assessment tools, such as sonAIR. This matter has been studied already for some examples on the component level, e.g., boundary layer ingestion noise is studied using both, analytical [61,62] and numerical approaches [63] or the Coanda flap, i.e., a high-lift device is studied regarding noise in [64][65][66] by means of numerical and experimental approaches. For the Coanda flap, even a system noise assessment is shown in [67].…”
Section: Discussionmentioning
confidence: 99%
“…Wake ingestion noise has received particular research interest for aircraft turbomachinery, including recent trends such as boundary layer ingestion into propulsion devices [145][146][147] and contrarotating open rotors. 107,148,149 The suitability of such existing noise prediction models for wake ingestion noise of eVTOL aircraft must be evaluated.…”
Section: Ingestion Noisementioning
confidence: 99%